2005
DOI: 10.1007/s11745-005-1387-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of polyunsaturated fatty acids including conjugated linoleic acids in total and subcellular fractions from healthy and cancerous parts of human kidneys

Abstract: Differences in the FA composition of subcellular fractions from healthy and cancerous kidney tissues from the same patients were examined. Only minor differences in CLA content were found between the healthy and the cancerous tissue portions. Regarding the distribution pattern, CLA incorporation into nuclei and cytosol was significantly higher than incorporation into plasma membranes and mitochondria, which could be correlated to the neutral lipid content of these fractions. The subcellular distribution patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
1
8
1
Order By: Relevance
“…This result is in agreement with our study of CLA in subcellular fractions of normal renal tissue and RCC where it was shown that CLA is best incorporated into nuclei and cytosol and significantly less into plasma membranes and mitochondria [21].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result is in agreement with our study of CLA in subcellular fractions of normal renal tissue and RCC where it was shown that CLA is best incorporated into nuclei and cytosol and significantly less into plasma membranes and mitochondria [21].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to TC, the total CLA content in RCC was found to be significantly increased in the plasma membrane fraction in comparison to the plasma membrane fraction of normal renal tissue [21], whereas no significant differences in the mitochondrial fractions of these two types of tissues were detectable.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…This subcellular distribution of PUFA has received minimal attention in the literature to date. However, differences in the fatty acid composition of human kidney nuclei, cytosol, plasma membranes and mitochondria subcellular fractions have been shown to vary in conjugated linoleic acid content [12]. Furthermore, rats fed corn oil diets versus fish oil diets had differential subcellular (nuclear matrix vs. membrane) n−3 and n−6 PUFA compositions [13].…”
Section: Discussionmentioning
confidence: 99%